Study of the sedimentological processes and evolution of the coastline of Marathon Bay - Schinias beach - Kourliaftis, G; Vandarakis, D.; Kapsimalis, V.; Vassilakis, E; Poulos, S.; Petropoulos, A. (12th Panhellenic Symposium of Oceanography and Fisheries, 2018)
The purpose of the study is the determination of the morphodynamical processes and the changes of the shoreline of Marathon Bay, which is located at northeast Attica. The area was lagoon 3.500 years BP (Pavlopoulos et al.2006) and it is characterized by low elevations and smooth slopes. The survey of the coastal and marine geomorphology was carried out by acoustic scanning of the seafloor with an echo sounder and sonar side scan topographical sections perpendicular to the shoreline and collection and analysis of surface sediments. The quantification of long-term shoreline displacements (Thieler et al. 2009) was carried out by comparing historical and recent aerial photographs (1945, 1960, 1969, 1988, 1996, 2001, 2010,), satellite imagery (6/2015, World View 2) and the imprint of the coastline (3/2013) with real time kinematic digital global positioning system (RTK DGPS). The estimation of rate and volume of the sediments transportation was realized by a hydrodynamical model (MIKE 21 Flow Model FM). At the north section of the area, near the estuary of Kainourio stream, and the lagoon’s draining channel, the maximum rates of coastal retreat are noticed (̴0,35m/year). The exposition of the coast to the southern waves, the reduced sediment supply from local rivers, due to the Marathon’s Dam and secondly of the morphology of their riverbeds, they have been filled because of the sea level rise the last 50yrs (IPCC, 2007). The lack of sediment supply, the sediment's composition and the morphological appearance of the submarine basin at the northeast of the Bay are mainly responsible for the coastal retreat along with the sea level rise.